Metformin Clinical Trial in HPV+ and HPV– Head and Neck Squamous Cell Carcinoma: Impact on Cancer Cell Apoptosis and Immune Infiltrate - Curry, Joseph M.; Johnson, Jennifer; Mollaee, Mehri; Tassone, Patrick; Amin, Dev; Knops, Alexander; Whitaker-Menezes, Diana; Mahoney, My G.; South, Andrew; Rodeck, Ulrich; Zhan, Tingting; Harshyne, Larry; et al. (Frontiers in Oncology, 2018)
Background: Tumor-driven metabolic dysregulation directly promotes tumor growth and also impacts stromal and immune elements of the tumor microenvironment (TME) in head and neck squamous cell carcinoma (HNSCC) and other cancers. This phenomenon is an active area of interest for development of targeted anticancer therapy. We previously conducted a clinical trial of metformin, an oral anti-hyperglycemic drug which inhibits mitochondrial complex I and oxidative phosphorylation (OXPHOS). We report new findings on the impact of metformin on the tumor and immune elements of the TME. Methods: Primary tumor samples from patients enrolled in a window of opportunity trial were analyzed by TUNEL assay to assess for apoptosis in cancer cells. Also, archival human papilloma virus (HPV)+ oropharyngeal (OPSCC) and HPV- HNSCC were compared for metabolic markers (MCT4, MCT1, TOMM20). Metformin treated metastatic lymph nodes with extra-capsular extension (ECE) were compared to archival lymph nodes with ECE for differences in immune markers quantified by digital image analysis using co-localization and nuclear algorithms (PD-L1, FoxP3, CD163, CD8). Results: Specimens from metformin treated subjects had a significantly higher increase in apoptosis in HPV- HNSCC (mean △ 13.7/high power field) compared to HPV+ OPSCC (mean △ 5.7/high power field) (p<0.001). Baseline HPV- HNSCC tumors and HPV+ OPSCC tumors differ in distribution of MCT4, MCT1, and TOMM20. These markers were not significantly altered in metformin treated specimens. However, on analysis of the stroma at the invasive front in ECE nodal specimens from both HPV- HNSCC and HPV+ OPSCC metformin treated specimens (mean 22.8%) showed increased CD8+ effector T cell (Teff) infiltrate compared to archival specimens (mean 10.7%) (p=0.006). Similarly, metformin treated specimens showed an increased FoxP3+ Treg infiltrate (mean 9%) compared to non-treated archival specimens (mean 5%) (p=0.019) Conclusions: This study presents novel preliminary data showing that metformin differentially impacts HNSCC subtypes with greater apoptosis in HPV- HNSCC compared to HPV+ OPSCC. Moreover, we present the first in vivo evidence that metformin may also trigger increased CD8+ Teff and FoxP3+ Tregs in the TME suggesting an immunomodulatory effect.